The Influence of Career Development and Work Motivation on Employee Loyalty at Hotel Pangeran - Orlen Dani Natsepa; Khairani Saladin (Pt. Threeple Herphi Educate, 2025)
This study investigates the influence of career development and job motivation on employee loyalty in the hospitality sector, focusing on Pangeran Beach Hotel Padang, Indonesia. A quantitative research design with a causal-associative approach was employed, using purposive sampling to collect data from 85 hotel employees. Data were obtained through a structured questionnaire measured on a five-point Likert scale and analyzed using multiple linear regression via IBM SPSS Statistics version 26.0. Instrument validity was confirmed through Pearson’s correlation, while reliability was assessed using Cronbach’s alpha, with all variables exceeding the 0.70 threshold. The results revealed that job motivation had a positive and significant effect on employee loyalty, whereas career development, although positively correlated, did not show a statistically significant independent effect. However, both variables jointly had a significant impact on loyalty, highlighting the synergy between long-term career planning and immediate motivational factors in strengthening workforce retention. These findings contribute to the theoretical development of employee loyalty models in emerging hospitality markets and provide practical guidance for hotel managers to prioritize motivation-enhancing strategies alongside structured career development programs